DISEASE BEARING INSECT RESEARCH IN MALAYA BY JAPANESE SCIENTISTS DURING WORLD WAR II AND ITS POSITION IN INTERNATIONAL LAW - Marina Abdul Majid (INTERNATIONAL JOURNAL OF LAW, GOVERNMENT AND COMMUNICATION (IJLGC), 2024)
Japanese scientists commissioned by the Imperial Japanese Navy (IJN) were tasked at the Nettai Igaku Kenkyusho or Institute of Medical Research (IMR) in Kuala Lumpur and other locations in Malaya during World War II (WWII) to identify cures for malaria, dengue, and scrub typhus rampant among Japanese troops in Southeast Asia. Such research on insects could contribute to biological warfare. This study identifies the background and destiny of these few Japanese scientists in Malaya conducting research on malaria, dengue and scrub typhus while evaluating if their research could have been an offense under international law at that point of time. A qualitative historical approach relying on documentation, soft law, treaties, and secondary resources obtained from archives and national libraries online from different countries and the Fold3-Historical Military Records website were referred. These documentations were classified according to names of Japanese scientists to form a short biography and to provide background information of the IMR during WWII. The results reveal some Japanese scientists responsible for malaria research at the IMR in Kuala Lumpur and Penang, and dengue research in Malaya, Singapore and Java. Human experimentation associated with dengue was suspected in Singapore. One IMR Japanese director had links with Unit 731. Kiyoshi Hayakawa, part of Unit 9420 in Singapore, Japan’s subunit for its covert biological weapons programme conducted research on scrub typhus in Java and Malaya. These scientists continued as professors in Japan or were promoted to this position much later with one of them opening a medical company. Indeed, a gap existed in international law at the end of the 19th and early 20th century which failed to make experimentation illegal as a preparation stage rather than actual usage in warfare because of the omission to address the development, production and stockpiling of biological weapons.